differenciate the following:

Asked by Ashish Kumar | 30th May, 2013, 10:43: AM

Expert Answer:

 y = (cosx+sinx)/(cosx-sinx)
dy/dx = [(cosx-sinx)(-sinx+cosx) - (cosx+sinx)(-sinx-cosx)]/(cosx-sinx)^2
dy/dx = [(cos2x+sin2x-2sinxcosx + cos2x+sin2x+ 2sinxcosx)]/(cosx-sinx)^2
dy/dx = 2/(cosx-sinx)^2
dy/dx = 1/(cosx*1/sqrt(2)-sinx*1/sqrt(2))^2
dy/dx = 1/cos(x+pi/4)^2
dy/dx = sec2(x+pi/4)

Answered by  | 31st May, 2013, 05:08: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.